ACCEPTABILITY OF KATURAY (SESBANIA GRANDIFLORA) AS PICKLES - Bogawit, Genevieve J.; Ganipac, Novelynne A.; Miranda, Britany C. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
The objective of this study was to assess the level of acceptance of katuray (sesbania grandiflora) pickles, specifically focusing on its sensory characteristics such as color, scent, taste, and texture. The study utilized a quasi-experimental methodology, with three different sample preparations, each with predetermined measures for the trial. A total of 50 persons from Bontoc, Mountain Province took part in data collection utilizing consumer-type panels. A 9-point hedonic scale was used to assess the acceptability of the katuray pickles. The participants were able to assess their degree of preference for each sensory characteristic using this scale. The data was subjected to statistical analysis, specifically analysis of variance (ANOVA), in order to interpret the data and ascertain the significance of variations in sensory qualities. The findings demonstrated that the flavor of katuray pickles was remarkably noteworthy, eliciting favorable comments from the subjects. In contrast, there were no notable disparities detected in the sensory characteristics of hue, fragrance, and consistency. This suggests that although flavor played an important role in determining the acceptability of the katuray pickles, other sensory characteristics did not have a substantial influence on the overall acceptability. This study indicates potential avenues for additional research and advancement. The researchers suggest exploring additional additives to enhance the pickled product. Furthermore, this study proposes further investigation into the unique characteristics of the katuray flower. Ultimately, this research proposes conducting a feasibility analysis in order to have a more comprehensive understanding of the market potential of the product that has been created.